Outcomes of Posterior Component Separation With Transversus Abdominis Muscle Release and Synthetic Mesh Sublay Reinforcement. Issue 2 (August 2016) - Novitsky, Yuri W.; Fayezizadeh, Mojtaba; Majumder, Arnab; Neupane, Ruel; Elliott, Heidi L.; Orenstein, Sean B.
Abstract : Objective: To evaluate the safety and efficacy of transversus abdominis muscle release (TAR) with retrorectus synthetic mesh reinforcement in a large series of complex hernia patients. Background: Posterior component separation via TAR during abdominal wall reconstruction (AWR) continues to gain popularity. Although our early experience with TAR has been promising, long-term outcomes have not been reported. Methods: From December 2006 to December 2014, consecutive patients undergoing open AWR utilizing TAR were identified in our prospectively maintained database and reviewed retrospectively. Main outcome measures included demographics, perioperative details, wound complications, and recurrences. Results: During the study period, 428 consecutive TAR procedures were analyzed. Mean age was 58, with mean body mass index 34.4 kg/m 2 (range 20–65). Major comorbidities included diabetes (21%), chronic obstructive pulmonary disease (12%), and immunosuppression (3%). Mean hernia defect area was 606 cm 2 (range 180–1280) and average mesh size was 1220 cm 2 (range 600–4500). The majority of cases (66%) were clean, 26% were clean-contaminated, and 8% were contaminated. Eighty (18.7%) surgical-site events occurred, of which 39 (9.1%) were surgical-site infections. Three patients required mesh debridement; however, no instances of mesh explantation occurred. Of the 347 (81%) patients with at least 1-year follow-up (mean 31.5 mo), there were 13 (3.7%) recurrences. Conclusions: Complex AWR represents a formidable surgical challenge. In this large series, we demonstrated that posterior component separation via TAR with wide synthetic mesh sublay provides a very durable repair with low morbidity, even in comorbid patients with large defects. We strongly advocate TAR as a robust addition to the armamentarium of reconstructive surgeons.